DESIGN AND IMPLEMENTATION OF REMOTE ENVIRONMENTAL DATA COLLECTING SYSTEM VIA ZIGBEE WIRELESS NETWORK FOR THE MUSEUM - INSTITUTE OF OCEANOGRAPHY - Tac, Vu Van; Phuc, Tran Tien; Cuong, Quach Duc (Vietnam Journal of Marine Science and Technology, 2014)
This paper presents the main specifications and the trial implementation results of remote environmental data collecting system via Zigbee wireless network. This system was designed and implemented by Institute of Oceanography and Faculty of Electrical and Electronic Engineering, Nha Trang Unisersity, in order to monitor remotely the environmental parameters of marine pond and tank system of  Oceanographic Museum - Institute of Oceanography. In this system, the environmental sensors are set-up at ponds and tanks. They automatically measure and send data to user’s computer and the data are saved in a database. The users can easily access this database to monitor the environment of the marine pond and tank system. This is the first step to lay the foundations for developing bigger applications to build a “Smart Museum” in the future.